Structural analysis, plastid localization, and expression of the biotin carboxylase subunit of acetyl-coenzyme A carboxylase from tobacco. - Shorrosh, B S (1995)
Acetyl-coenzyme A carboxylase (ACCase, EC 6.4.1.2) catalyzes the synthesis of malonyl-coenzyme A, which is utilized in the plastid for de novo fatty acid synthesis and outside the plastid for a variety of reactions, including the synthesis of very long chain fatty acids and flavonoids. Recent evidence for both multifunctional and multisubunit ACCase isozymes in dicot plants has been obtained. We describe here the isolation of a tobacco (Nicotiana tabacum L. cv bright yellow 2 [NT1]) cDNA clone (E3) that encodes a 58.4-kD protein that shares 80% sequence similarity and 65% identity with the Anabaena biotin carboxylase subunit of ACCase. Similar to other biotin carboxylase subunits of acetyl-CoA carboxylase, the E3-encoded protein contains a putative ATP-binding motif but lacks a biotin-binding site (methionine-lysine-methionine or methionine-lysine-leucine). The deduced protein sequence contains a putative transit peptide whose function was confirmed by its ability to direct in vitro chloroplast uptake. The subcellular localization of this biotin carboxylase has also been confirmed to be plastidial by western blot analysis of pea (Pisum sativum), alfalfa (Medicago sativa L.), and castor (Ricinus communis L.) plastid preparations. Northern blot analysis indicates that the plastid biotin carboxylase transcripts are expressed at severalfold higher levels in castor seeds than in leaves.